ON THE MEANING OF CITY WALLS IN LATE ROMAN SPAIN - Adriaan De Man (Journal of Ancient History and Archaeology)
During three or four decades of the late 3rd and early 4th century, a number of cities across the Empire were refortified in a pattern that cannot be explained in defensive terms alone. Regional and especially local authorities seem to have played a decisive role in the process, and Lusitania is a clear case of non-military initiative. About a dozen sites, a minority that is, did invest in these new structures, which were highly disruptive to daily life, private property, and public resources. These same cities would find a relevance in the post-Roman world, as bishoprics and as military structures, an argument probably absent in their original builders’ purpose.